Pengaruh Komisaris Independen, Intensitas Modal, dan Kompensasi Eksekutif Terhadap Agresivitas Pajak - Muhamad Noval Aditia; Dirvi Surya Abbas; Samino Hendrianto (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The purpose of this study is to determine the effect of independent commissioners, capital intensity, and executive compensation on tax aggressiveness in moderating institutional ownership in property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2021 period.This study uses a quantitative approach. The population in this study is 80 property and real estate companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling. The criteria that have been set are obtained from 8 samples of Property and Real Estate companies. The type of data used in this research is secondary data. The method used in this research is panel data regression analysis.The results of this study indicate that the Independent Commissioner has a positive effect on Tax Aggressiveness. Capital Intensity has a negative effect on Tax Aggressiveness. Executive Compensation has no effect on Tax Aggressiveness. Ownership of the Memorandum of Institutional Relations on Tax Aggressiveness has a negative effect. Ownership of the Institutional Relationship between Capital Intensity and Tax Aggressiveness has a positive effect. Institutional Ownership cannot moderate the relationship between Executive Compensation and Tax Aggressiveness.